Participatory Varietal Selection and Agronomic Evaluation of African Eggplant and Roselle Varieties in Mali - Diouf, Meissa.; Gueye, Mathieu; Samb, Papa Ibra (European Scientific Journal, ESJ, 2017)
African eggplant (Solanum aethiopicum L. and S. macrocarpon L.) is one of the most commonly consumed fruit vegetables in tropical Africa, in quantity and value probably the third after tomato and onion. Commercial production for supply to the cities is increasing. Roselle (Hibiscus sabdariffa L.) is another important vegetable crop in sub-Saharan Africa; its leaves, seed, and calyces are eaten. Roselle leaves and calyces are nutritious and rich in iron, β-carotene, and ascorbic acid. Although there is a market for African eggplant and Roselle, farmers have been slow to adopt new improved varieties due to use of traditional breeding method. To increase adoption rates of new varieties, we used a participatory varietal selection process to identify new varieties of both plants based on fruit yield, leaf, calyx traits, and consumers’ preference. Fifteen lines and varieties of each species from several African countries were evaluated in Bamako, Mali during the 2008 hot rainy season. A randomized complete block design with three replications was used for the selection process. Twenty-two vegetable farmers and traders (or users) from Bamako rated the African eggplant and Roselle varieties based on visual characteristics (fruit color, fruit shape, number of fruits per plant, fruit size, number of secondary branches per plant, leaf size, leaf shape, leaf color, number of calyces per plant, calyx shape, and calyx color). Using a scale from 0 (least preferred) to 5 (most preferred), the varieties and the criteria were ranked, to identify the best variety and the most important criteria. In addition, agronomics data of African eggplant (number of fruits per plant, marketable yield, fruit weight, fruits shape and fruit color) were collected. Agronomics data were also collected on Roselle calyces (number of calyces per plant, fresh calyces yield, dry calyces yield, dry matter and calyces color based on stem color) and leaves production (leaf length and width, economic yield, leaf shape and stem color). African eggplant line L10, varieties Soxna and Locale Gaya were highly rated for their visual appeal and have the potential to out-yield the local Malian variety. The fruit color and fruit shape, classified top two criteria through participatory selection criteria are important in the choice of users. For leafy entries of Roselle, leaf size was the most important trait. Samandah and line L28 were rated higher than the local check variety (Dah Rouge) for all traits. For calyx varieties of roselle, the number of calyces per plant was the most important trait. For leafy and calyx varieties, the agronomic evaluation show that yield is not a very important criterion in the choice of the users.